THE USE OF DOMESTIC ANIMAL TERMS (CAMEL) IN KARAKALPAK PROVERBS AND SAYINGS - Dilanov, Bekmurza Gulimbetovich (SCIENCE and SOCIETY, 2026)
The article examined animal terms used in Karakalpak proverbs and sayings from a linguocultural perspective. By studying paremiological units, we obtain a lot of information about the life, lifestyle, culture, and vocabulary of the Karakalpaks. Because proverbs and sayings contain words related to the original vocabulary of the people.
Keywords: zoomorphism; animalism; paremias; karakalpak language; linguoculturology; mythology; ethno-culture; imagery